A qualidade na educação infantil brasileira : uma revisão necessária - Grando, Marina Schnorr (2014)
This paper aims to discuss the concept of quality in early childhood education present in the official formulations that address this Basic Education stage. Therefore, desk research of which took part the following documents has been developed: Federal Constitution, 1988; Statute of Children and Adolescents, 1990; Law of Directives and Bases of National Education, 1996; National Education Plan, 2001; National Quality Parameters for Early Childhood Education, Volumes 1 and 2, 2006; Quality indicators in Early Childhood Education, 2009; Quality Monitoring in Early Childhood Education and Executive Summary, 2011. To discuss laws and selected documents, we used the content analysis procedure, checked against the following theoretical frameworks Barros, 2013; Campos, 2011; Craidy, 2001; Dahlberg, 2003; Zabalza, 1998. In this work, the categories that describe the understanding of what constitutes quality in early childhood education were as follows: Implemented pedagogical intent through documents such as pedagogical and curricular proposals; training and continuous improvement of the professionals involved; partnership with the government, with the families, the school community and the social safety net; ensuring the rights and children's needs, integrating the actions of caring for and educating, valuing the affection, the languages, the emotional aspects, interactions and seeking health promotion in schools; individualized attention to children and their way of learning, balancing the role of the teacher and the children's initiative; physical space, materials and the space-time organization, establishing stable routines